Tendencies in Latgale museums’ work for the maintenance and popularization of culture heritage - Burceva, Rita (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The objective of the research is to describe the traditional and innovative trends of Latgale region museums’ work in the field of culture heritage’s maintenance and popularization. The analysis of the documents and theoretical sources, the experience of reflection, the narrative approach are the methods that have been used in the research. Both municipality and private museums work in Latgale and most of them are characterised by the following development tendencies in the maintenance of culture heritage: the search of their own uniqueness and peculiarities, a modern interpretation of the existing museum collections, the interaction of modern culture expressions and cross-cultural communication, the pedagogical function of the museums, the development of museums’ informative environment.